2007
DOI: 10.1111/j.1365-2516.2006.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous liver biopsy in adult haemophiliacs with hepatitis C virus: safety of outpatient procedure and impact of human immunodeficiency virus coinfection on the spectrum of liver disease

Abstract: Both HCV and HIV are common in haemophiliacs previously treated with non-viral-inactivated clotting factor concentrates. Because of increased bleeding risks, little data are available on the safety of percutaneous outpatient liver biopsy (LBx) and impact of HIV coinfection in this population. This study aims at reporting our experience with percutaneous LBx in a cohort of haemophiliacs infected with HCV and describe the spectrum of disease and impact of HIV coinfection. A retrospective review of consecutive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
(96 reference statements)
1
8
0
Order By: Relevance
“…Especially in hemophilia patients, measurement of prothrombin time or INR is not often carried out because of the apparent abnormal value expected. Therefore, the ALICE score or the APRI and FIB‐4, which was also reported by our group previously, could be useful markers for non‐invasive monitoring tools, as both are correlated with the severity of liver fibrosis and/or cirrhosis as a surrogate indicator for detecting esophageal varices …”
Section: Discussionsupporting
confidence: 64%
“…Especially in hemophilia patients, measurement of prothrombin time or INR is not often carried out because of the apparent abnormal value expected. Therefore, the ALICE score or the APRI and FIB‐4, which was also reported by our group previously, could be useful markers for non‐invasive monitoring tools, as both are correlated with the severity of liver fibrosis and/or cirrhosis as a surrogate indicator for detecting esophageal varices …”
Section: Discussionsupporting
confidence: 64%
“…Literature review. A total of 26 papers published between 1977 and 2007 were reviewed [49–74] (Table 3). These studies included 778 procedures performed in 713 patients (Haemophilia A: 526; Haemophilia B: 68; unspecified: 119).…”
Section: Resultsmentioning
confidence: 99%
“…HCV/HIV coinfection is associated with increased rates of fibrotic progression, higher rates of cirrhosis in cross-sectional analyses and more rapid progression to end-stage liver disease compared to those with either HCV or HIV monoinfection 2–7. An analysis comparing HCV monoinfected and coinfected hemophilics showed that coinfection was associated with higher fibrosis scores and a higher proportion of advanced fibrosis/cirrhosis after controlling for age, demographic features or other laboratory parameters 8. Treatment of HCV in the setting of HCV/HIV coinfection yields suboptimal results with a significant decrement in sustained viral response compared to those with HCV monoinfection who undergo interferon-based therapies 9…”
Section: Introductionmentioning
confidence: 99%